Energy and exergoeconomic analyses of parallel cross feed multi effect desalination system driven by twin-screw compressor with water injection - Osman Shamet; Mohamed A. Antar (Case Studies in Thermal Engineering, 2024)
This work proposes the design of a parallel cross-feed multi-effect desalination system with a twin-screw compressor, incorporating water injection to enhance system performance. The improvement is achieved by injecting water during the compression process to increase the isentropic efficiency of compression. The mathematical model is solved using Engineering Equation Solver software, and the resulting mass and energy balance equations are validated against literature data. The system is analyzed and evaluated from energy, exergy, and exergy-economic perspectives, and compared with the performance of the conventional configuration in terms of specific power consumption, exergy efficiency, and cost of produced water. The impact of various operating conditions, such as the number of effects, steam temperature, compressor efficiency, and injection pressure, on specific power consumption, exergy efficiency, exergy destruction, and final product cost, is examined in this study. Additionally, factors like interest rate, plant life expectancy, and electricity cost are investigated for their effect on the final product cost. The study demonstrates that replacing the normal compressor with a twin-screw compressor result in more than a 15 % reduction in specific power consumption, approximately 4 % less exergy destruction (indicating higher exergy efficiency), and a 14 % lower unit cost of freshwater.